Utilization of Local Product for Complementary Food Menu in Stunting Prevention - Witri Dewi Mentari; Nurce Arifiati; Marthia Ikhlasiah; Ismarina; Agung Sutriyawan (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Giving complementary breastmilk (MP-ASI) food needs to be given in the first six-months to reach the goal of optimal growth and development of baby. Nutritional intake of the baby needs to be monitored for the sake of it would be irreversible if the it not had been monitored. The aims of this research is to increasing the knowledge about the utilization of local product for complementary food menu in stunting prevention. The counselling was carried out on Wednesday, February 1st 2023, at the Pamengkang Village, Kramatwatu district, Serang regency. In the counselling, there were 50 participants from the target participant, such as, pregnant mother, mother with baby and child. The event was using the speech and advocate from the expert. The counselling would hope that all the participants realized about the various local product that can be used to make complementary food.